Diversity of Weevils (Coleoptera) in Marahan, Marilog Forest Reserve, Southern Mindanao, Philippines - Mohagan, Alma B.; Patano, Romeo Jr. Rogano; Melencion, Merced G.; Salas, Daryl S.; Coritico, Fulgent P.; Amoroso, Victor B. (Journal of Tropical Life Science, 2020)
Fieldworks were conducted last January to March, 2019 to collect and record species of weevils at Sitio Matigsalug, Marahan, Marilog Forest Reserve, Marilog District, Mindanao, Philippines. Standard sampling techniques such as belt transect and opportunistic sampling were conducted in the established 2 kilometers transect to survey the agroforest and montane ecosystems with elevations of 800-950 masl and 1,000-1,300 masl, respectively. A total of 228 individuals belonging to 2 families and 22 species of weevils were recorded, all of which are only known from forest and mountain ecosystems of Mindanao. Metapocrytus is the most encountered genus with 12 species. The montane forest had higher species richness with 15 species but with lower species abundance of 34 individuals compared to the agroforest ecosystem with 13 species and 194 individuals. Seven (7) species are common in both sites. Plant associates and behavior of the observed weevils were also noted which include 22 species of ferns and flowering plants. Other than perching behavior, species are also observed copulating, feeding and mostly hiding in abaxial part of leaves. As flightless beetles with high vulnerability for predation by other insectivorous species, the observations gathered will help in understanding their behaviors for survival. Despite of high species richness and abundance, anthropogenic disturbances such as agricultural activities are on-going which extend towards the montane forest in the area. Conservation initiatives must be implemented to protect the remaining endemic and rare species of flora and fauna.